A Nonbalancing Act: Explaining Indonesia's Failure to Balance Against the Chinese Threat. Issue 3 (2nd September 2017) - Syailendra, Emirza Adi
ABSTRACT: Indonesia faces an increasing maritime threat from China. Incursions of China's maritime law enforcement forces protecting Chinese ships fishing illegally in Indonesia's Exclusive Economic Zone pose a threat to President Joko Widodo's goal of transforming Indonesia into a Global Maritime Fulcrum. China's actions generate the prediction that Indonesia should balance against China, but this has not occurred. Instead, bureaucratic politics and President Jokowi's interest in securing Chinese financial support for his ambitious infrastructure projects have prevented the adoption of a more assertive balancing policy. Using Schweller's argument that threats go unanswered when there is disagreement among key domestic actors, this article argues that a lack of elite consensus in Indonesia is impeding the adoption of a balancing policy. Instead, Indonesia is continuing its traditional policy of nonbalancing .